Innovative models of flexible final customers in operation of smart distributed energy systems : doctoral thesis - Gržanić, Mirna (M. Gržanić ; Faculty of electrical engineering and computing, 2022)
The increasing share of renewable energy sources (RES) is one of the main goals in the transition towards a carbon-neutral power system. Due to their intermittent nature, RES require an additional level of flexibility to ensure stable and secure power system operation. In the past, the flexibility used to be provided from conventional power plants, such as coal power plants which are less flexible and open-cycle gas turbine (OCGT) and natural gas-fired internal combustion engine (ICE) power plants with a high level of flexibility characterized with short minimum uptime and minimum downtime, short start-up time and low start-up cost. However, the enlarged need for flexibility in green energy transitions opens the doors for providing system services from the end-user's side. The role of final customers has been under significant changes. From completely passive entities, final customers are becoming active network participants involved in the real-time (RT) power system operation. With the recent price decrease of low carbon technology, more final customers tend to invest in photovoltaic (PV) systems, household battery energy storage (BES), electric vehicles (EV), and household energy management systems (HEMS). To fully exploit their potential, European directives highlight the importance of providing transparent and easy-to-understand pricing mechanisms together with pricing comparison tools in order to ensure fair and the most economic solutions to all final customers. As some final customers, such as households, are too small to independently trade their flexibility on the market, a new market entity called aggregator gathers their flexibility potential and trades with their services on the market. Final customer's flexible behaviour can be remunerated through direct incentives, electricity bill reduction or even a discount for investing in low-carbon technology and fixed annual direct payments for flexible management of different household appliances. The thesis investigates the impact of diverse pricing mechanisms on the behaviour of final customers, their consumption profile, and electricity bill in different European countries considering not only energy prices, but also transmission and distribution network charges, tax, VAT, and the pricing policy related to RES installed at final customer's side. Flat prices, two-tariff pricing, and RT dynamic pricing for prosumers are compared resulting in more flexible behaviour and electricity bill reduction under dynamic prices. In general, the current pricing structure encourages final customers with installed RES to shift their flexible consumption in the periods of high production, instead of selling excess to the supplier. Furthermore, the thesis deals with different forms of aggregation resulting not only in financial benefits to all entities involved but also reducing the negative impact of the intermittent nature of RES. The first type of aggregation investigated in the thesis is a formation of an innovative balancing group (BG) composed of the aggregator of flexible prosumers and a wind power plant (WPP) participating in the day-ahead (DA) energy market and balancing market. The focus is put on joint market participation which reduces prosumers' electricity cost and increases WPP profit due to decreased balancing cost arising from flexible behaviour of final prosumers which serve as a buffer between balancing market and the intermittent and variable WPP's production. The second type of aggregation in the thesis is focused on an energy community. The energy community will participate in the power system transition by allowing the participation of citizens in the clean energy transition in diverse legal forms, such as associations, cooperatives, partnerships, non-profit organizations, and small/medium enterprises. Community members investigated in the thesis are equipped with PV, flexible electric heating, flexible household appliances, and have an opportunity of smart EV charging. The community is operated by the community manager (CM) who is in control of flexible household devices through HEMS. The CM tackles the issue of the stochastic nature of PV and households' consumption by providing flexibility incentives to community members in order to reduce the deviation from preannounced DA schedule. The energy community participates on the market as a single entity and the cost of community members is calculated ex-post, after energy delivery which makes the optimization algorithm simple to solve. Prices for the internal energy exchange between community members are calculated based on three pricing mechanisms: Bill Sharing Method Net (BSMN), Mid-Market Rate Net (MMRN), and Supply Demand Ratio Net (SDRN) taking into account the net load of each community member, DA energy prices and flexibility incentives. Participation in the energy community together with the price calculation developed in the thesis which is conducted in a two-stage process guarantee lower electricity cost to each community member compared to their individual contract with the supplier.